(untitled) (Journal of Atomic and Molecular Sciences, 2012)
We investigate the spin current through a molecular quantum dot (MQD) irradiated with a rotating magnetic field and an oscillating magnetic field by nonequilibrium Green's function. The rotating magnetic field rotates with the angular frequency ω_r around the z-axis with the tilt angle θ, and the time-oscillating magnetic field is located in the z-axis with the angular frequency ω. Different behaviors have been shown in the presence of electron-phonon interaction (EPI) which plays a significant role in the transport. The spin current displays asymmetric behavior as the source-drain bias eV=0, novel side peaks or shoulders can be found due to the phonon absorption and emission procedure, and the negative spin current becomes stronger as the parameter g increases. However, the spin currents display the same magnitude and the same oscillation behavior in the region μ_0B_1>3Δ regardless of the parameter g.